Discussion on the training mode of Traditional Chinese Medicine nursing inheritance talents (中医护理传承人才培养模式探讨) - LI Ye (李野); E HaiYan (鄂海燕); Tang Ling (唐玲) (Association of Integrative Nursing, 2023)
Traditional Chinese Medicine (TCM) nursing talents are the carrier of the inheritance, innovation and development of the valuable experience of TCM nursing. Optimizing TCM nursing talent training mode, speeding up the TCM nursing personnel training, improving the quality of TCM nursing personnel training are is of crucial importance for the revitalization of TCM nursing. This paper aims to actively explore the TCM nursing inheritance talent cultivation strategy, strive to realize the TCM nursing from generation to generation, promote the innovation and development of TCM inheritance, and provide reference for promoting the construction of make greater contribution to healthy China. (中医护理人才是中医护理宝贵经验得以继承、创新、发展的载体。优化中医护理人才培养模式、加快中医护理人才培养速度、提高中医护理人才培养质量是振兴中医护理事业的重要内容。本文旨在积极探讨中医护理传承人才的培育策略, 力求实现中医护理代代薪火相传, 促进中医药传承创新发展, 为推进健康中国建设作出贡献。)